The democracy and economic growth nexus: Do FDI and government spending matter? Evidence from the Arab world - Nouha Bougharriou; Walid Benayed; Foued Badr Gabsi (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
The purpose of the paper is to examine the direct and indirect links between democracy and economic growth. To do so, the authors estimate a dynamic panel simultaneous equations model on a sample of 16 Arab countries during the period 2002-2013. This study focuses on two particular channels through which democracy affects growth, namely FDI inflows and public consumption expenditure. The results show that there is no clear relationship between democracy and economic growth in the Arab countries, which confirms the skeptical approach. The ambiguity of this relationship can be explained by the fact that democracy promotes growth indirectly by stimulating FDI inflows and hinders growth by generating higher public consumption expenditure.
http://dx.doi.org/10.7910/DVN/NUD3G6
Keywords: C3; O40; P16; 330; democracy; economic growth; FDI; government spending; Arab world; dynamic panel simultaneous equations model